POTENCIAL DE CULTIVARES DE BATATA-DOCE PARA PRODUÇÃO DE ÁLCOOL - KOPF, CRISTIANE (2018)
Due to the environmental problems that the planet is facing in relation to the emissions of carbon dioxide in the atmosphere, it is necessary to make feasible researches to control the damages caused by such emissions. The objective of this study was to produce alcohol from sweet potato flour of nine cultivars, and to evaluate which one has the highest yield in terms of production. This raw material is a promising crop when compared to others, as far as the production of biofuel is concerned. Physical and chemical analyzes were performed: moisture, ash, lipids, proteins, fibers for raw sweet potato and also starch, reducing sugars and total reducing sugars for sweet potato flour. In addition, we evaluated the yield in terms of alcohol yield obtained, the alcohol content and performed infrared spectrum analysis. The alcohol was produced from the acid hydrolysis and the alcoholic fermentation was performed in the parameters: pH 5.0; temperature of 25 °C and time of 5 days. The characterization of raw sweet potato and sweet potato flour presented satisfactory percentages, consistent when compared to other authors and also with the legislation. From the calculation of the alcohol production estimate, the highest value was obtained for 16034.06 ± 1.12 L.ha-1 for Laranjeiras 3. In relation to the percentage of alcohol content, values between 9.13 and 14.25% were found. In the infrared spectrum analysis, functional groups of alcoholic compounds of 3417 cm-1, related to the O-H stretching and 1388 cm-1, representing the angular deformation of O-H and the stretching of C-O were determined. Thus, sweet potato is a promising alternative for the production of biofuels, presenting satisfactory results.